Boosting Literacy: Evaluating the Impact and Satisfaction of Project DARA (Daily Reading Activities) - Sales, Joewe (Journal of Interdisciplinary Perspectives, 2024)
This study provides a comprehensive analysis of pre-reading activities, post-reading activities, and satisfaction levels across several dimensions: Program Experience, Reading Improvement, Personal Impact, and Program Feedback, as detailed in various tables. The pre-reading activity highlighted significant gender disparities and varying difficulties with word lengths across different grades. The post-reading assessment demonstrated substantial progress in reading abilities across all grade levels, affirming the program's effectiveness. The findings revealed notable gender disparities in learner distribution across all grades, with a higher number of female learners, indicating the need for tailored interventions. The post-reading assessment showed significant improvements in reading abilities, including comprehension, speed, and fluency, across all grades. Learners exhibited increased confidence, engagement, and motivation, with some even tutoring peers, underscoring the program's impact beyond technical skills. Additionally, participants reported high satisfaction levels across various aspects of the program, including organization, materials, instructor quality, and program content. They experienced increased confidence, independence, enjoyment of reading, and improved academic performance, indicating a positive personal impact. This research underscores the efficacy of the 90-day reading program in addressing foundational literacy challenges, fostering independent reading habits, and positively influencing learners' personal and academic lives. The findings emphasize the importance of tailored interventions, supportive environments, and ongoing support in enhancing reading abilities and promoting lifelong learning.